Efficacy of toric intraocular lens implantation in individuals with cataracts and asymmetric corneal astigmatism - Jiezheng Xue; Anpeng Pan; Xu Shao; Xu Xu (Photodiagnosis and Photodynamic Therapy)
Objective: The objective of this study is to evaluate the efficacy and safety of toric intraocular lens (IOL) implantation in individuals with cataracts and asymmetric corneal astigmatism and to assess their postoperative visual quality. Methods: In this prospective case series, 26 eyes of individuals with cataracts and corneal astigmatism > 0.75 diopters (D) and asymmetric central astigmatism as identified through corneal topography were examined at the Eye Hospital of Wenzhou Medical University, China. All participants underwent toric IOL implantation surgery at the hospital. The primary outcome measures included uncorrected visual acuity (UCVA), best corrected visual acuity (BCVA), residual astigmatism, prediction error, and the degree of IOL rotation. Results: Both postoperative UCVA and BCVA improved significantly, with UCVA increasing from 0.70 (0.40, 0.93) to 0.018 (0.05, 0.30) logMAR, and BCVA improving from 0.50 (0.38, 0.70) to 0.00 (0.0, 0.10) logMAR (P < 0.001). A strong positive correlation was observed between the preoperative predicted spherical equivalent and the postoperative actual spherical equivalent (= 0.7682), with prediction errors for the spherical equivalent within ± 1.00 D in all cases. Postoperative residual astigmatism was ≤ 1.00 D in 25 eyes (96%), and the mean degree of toric IOL rotation was 2.46° ± 2.08°. Objective assessments of visual quality showed that patients with asymmetric corneal astigmatism achieved better postoperative visual quality under miotic conditions (pupil diameter: 2 mm), with a significant decrease in visual quality as pupil diameter increased. Conclusion: The results of this study demonstrated that toric IOL implantation surgery is an effective and safe treatment for selected individuals with cataracts and asymmetric corneal astigmatism. Preoperative predictions for spherical equivalent and residual astigmatism in these patients proved accurate and reliable, resulting in favorable visual outcomes and enhanced visual quality post-surgery.